Prevalence of crustacean parasites infecting cultured fish in Peninsular Malaysia - Mohammed, Ibrahim (2017)
Crustacean parasites are among the most harmful pest of fishes infecting cultured fish. The present study aims at determining the prevalence of crustacean parasites and anti-parasitic effect of herbs in controlling the parasites currently infecting grow-out fish farms in Peninsular Malaysia. Eleven fish farms were visited to identify fish infested with crustacean parasite. A total of 510 fish consisting of 100 snakehead (Channa striatus), 250 grouper (Epinephelus fuscoguttatus) and 160 goldfish (Carassius auratus) were collected randomly from different areas from January to December 2013. Based on the sampling locations, the prevalence of isopods was generally higher in two sampling areas, i.e. in the South of Peninsular Malaysia (97.5%) and the Central (90%) as compared with Argulus sp. that was high in the north of Peninsular Malaysia (92%) but moderate in the Central (74.3%). Our results showed a significant difference in prevalence of these parasites within the three sampling areas. Prevalence of Argulus sp. was found to be higher in snakehead (92%) as compared to goldfish (70%). Our results also showed significant difference in mean intensity values of Argulus infestation between snakehead and goldfish. Three herbs extracts namely neem leaves (Azadirachta indica), wormseed plant (Artemesia cina) and German chamomile (Matricaria chamomilla) were selected to investigate their potential antiparasitic action on Argulus sp. and isopods in in vitro assay. The ectoparasites were exposed to 10, 25, 50, 75 and 100 mg/L of herb concentrations and the mortality was compared with the control groups which used fresh and marine water without addition of any herb extract. In vitro study showed Argulus sp. mortality for all the concentrations of neem leaves, chamomile and wormseed plant extracts. A significantly high anti-parasitic effect of these herbs extract solution was observed at concentration of 100 mg/L. In vitro study with isopods also showed mortality of the parasites for all the different treated concentration of neem leaves, chamomile and wormseed plant extracts. The results demonstrated that the three herbs showed high anti-parasitic effect towards crustacean parasites tested. The herbs extracts were also tested against Argulus sp. infested goldfish. The short-term static toxicity test was carried out to determine the median lethal concentration (LC50) of three herbs on goldfish. The immersion experiment was performed using 50, 100 and 150 mg/L of the herbs extracts for 96 hr, along with control in well aerated water in glass aquaria. The concentration of neem extract, in which 50% of the goldfish were killed in 96 hr was 160 mg/L. In vivo artificial cohabitation Argulus sp. infection test was carried out using naive goldfishes with an average weight of 20-22g. Results showed an average attachment of Argulus sp. ranged from 2-5 parasites per fish during two weeks exposure. In another in vivo assay, goldfish infested with at least three Argulus sp. were treated with bath treatment using two concentrations of herbs (50 and 100 mg/L). Results showed that the three herbs extract were able to reduce the parasites burden and showed anti-parasitic effects on Argulus sp. Three herbs extract at 100 mg/L was tested in tiger grouper infested with one isopod in buccal cavity and the result revealed that neem leaves, chamomile and wormseed plants showed anti-parasitic properties in marine environment and could reduce isopod burden on fish. Analysis of survival using Kaplan-Meier showed that all treatment using the selected herbs in goldfish and tiger grouper showed significant anti-parasitic properties against Argulus sp. and isopod. The efficacies of the three herbs were considered as time-dependent since mortalities increased with longer exposure time. In conclusion, neem leaves, chamomile and wormseed plant extracts showed the ability in controlling the crustacean parasites tested and have potential as anti-parasitic agent in aquaculture.